Transtracheal single-point stent fixation in posttracheotomy tracheomalacia under cone-beam computer tomography guidance by transmural suturing with the Berci needle - a perspective on a new tool to avoid stent migration of Dumon stents - Hohenforst-Schmidt, Wolfgang; Linsmeier, Bernd; Zarogoulidis, Paul; Freitag, Lutz; Darwiche, Kaid; Browning, Robert; Turner, J. Francis; Huang, Haidong; Li, Qiang; Vogl, Thomas; Zarogoulidis, Konstantinos; Brachmann, Johannes; et al. (Therapeutics and Clinical Risk Management, 2015)
Tracheomalacia or tracheobronchomalacia (TM or TBM) is a common problem especially for elderly patients often unfit for surgical techniques. Several surgical or minimally invasive techniques have already been described. Stenting is one option but in general long-time stenting is accompanied by a high complication rate. Stent removal is more difficult in case of self-expandable nitinol stents or metallic stents in general in comparison to silicone stents. The main disadvantage of silicone stents in comparison to uncovered metallic stents is migration and plugging. We compared the operation time and in particular the duration of a sufficient Dumon stent fixation with different techniques in a patient with severe posttracheotomy TM and strongly reduced mobility of the vocal cords due to Parkinson's disease. The combined approach with simultaneous Dumon stenting and endoluminal transtracheal externalized suture under cone-beam computer tomography guidance with the Berci needle was by far the fastest approach compared to a (not performed) surgical intervention, or even purely endoluminal suturing through the rigid bronchoscope. The duration of the endoluminal transtracheal externalized suture was between 5 minutes and 9 minutes with the Berci needle; the pure endoluminal approach needed 51 minutes. The alternative of tracheobronchoplasty was refused by the patient. In general, 180 minutes for this surgical approach is calculated. The costs of the different approaches are supposed to vary widely due to the fact that in Germany 1 minute in an operation room costs on average approximately 50-60EUR inclusive of taxes. In our own hospital (tertiary level), it is nearly 30EUR per minute in an operation room for a surgical approach. Calculating an additional 15 minutes for patient preparation and transfer to wake-up room, therefore a total duration inside the investigation room of 30 minutes, the cost per flexible bronchoscopy is per minute on average less than 6EUR. Although the Dumon stenting requires a set-up with more expensive anesthesiology accompaniment, which takes longer than a flexible investigation estimated at 1 hour in an operation room, still without calculation of the costs of the materials and specialized staff that the surgical approach would consume at least 3,000EUR more than a minimally invasive approach performed with the Berci needle. This difference is due to the longer time of the surgical intervention which is calculated at approximately 180 minutes in comparison to the achieved non-surgical approach of 60 minutes in the operation suite.
EVALuna2:12091